2019
DOI: 10.1021/acs.energyfuels.9b02781
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Composition and Content of Dissolved-State Paraffins in Model Oil on the Aggregation State of Asphaltenes and the Stability of Water-in-Model Oil Emulsion

Abstract: Paraffins cause many issues during the production and transportation of crude oils. To date, there is abundant research on the rheological properties of crude oils after paraffin crystallization and the effect of precipitated wax particles on the stability of water-in-crude oil (w/o) emulsions. However, the impact of dissolved-state paraffins on w/o emulsion stability is insufficiently studied. This article focuses on the effect of dissolved-state paraffins with different carbon number distributions (CNDs) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…However, there is still a decrease in the interfacial tension with time for the pure waxy oil. This phenomenon is also found in other studies and probably due to the presence of trace impurities in the solvent which have amphiphilic properties. , …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…However, there is still a decrease in the interfacial tension with time for the pure waxy oil. This phenomenon is also found in other studies and probably due to the presence of trace impurities in the solvent which have amphiphilic properties. , …”
Section: Resultssupporting
confidence: 81%
“…This phenomenon is also found in other studies and probably due to the presence of trace impurities in the solvent which have amphiphilic properties. 50,51 What is more important is the relation between the other two interfacial tensions shown in Figure 8 at different temperatures. The dynamic interfacial tension of the model oil containing both paraffin wax and GMO almost overlaps with that of the mineral oil containing only GMO when the temperature stays above the WPT (Figure 8a).…”
Section: Stabilitymentioning
confidence: 99%
“…For waxy oil emulsions, the wax crystals themselves cannot be adsorbed at their interfaces because the precipitated wax crystals have no interfacial activity . However, for crude oil emulsions, wax affects the emulsion properties through two aspects: first, the apparent viscosity change caused by wax affects the aggregation of emulsion droplets; second, the wax crystals, especially after cocrystallization adsorption with colloidal asphaltene, will precipitate at the oil–water interface affecting emulsion stability. − Chen et al studied a model oil–water emulsion system and found that if the wax molecules can cocrystallize with the emulsifier, the emulsifier will promote the adsorption of wax molecules at the oil–water interface, forming an elastic interfacial film and preventing the agglomeration of water droplets. If the wax molecules cannot cocrystallize with the emulsifier, the wax molecules will not crystallize at the water droplet interface.…”
Section: Wax: Structures and Thermodynamic And Phase Behaviorsmentioning
confidence: 99%
“…Over several decades, extensive theoretical and experimental efforts have been made to study the interactions between asphaltenes and waxes and their effect on deposit formation. − The phenomena derived from these interactions are still far from being completely understood. There is still neither a generalized model nor a theory that can completely explain contradictory experimental data.…”
Section: Introductionmentioning
confidence: 99%